Analysis of Rear Wheel Traction Force with Rim Variations on the Surface Morphology of 90/80 Tire Size Using Image-J Software - Mohamad Rendi Zulifikar; Dewi Sartika; M. Khoirul Anam (Fakultas Teknik Universitas PGRI Banyuwangi, 2025)
Motorcycles are the dominant means of transportation in Indonesia. The land transportation population in Indonesia in 2021 was 141,992,573. Motorized vehicles are predominantly motorcycles, with 120,042,298 users. According to the 2021 report by the Indonesian Statistics Agency (BPS), the number of motorcycles continues to increase by an average of 4.62% per year. Aluminum rims are the most widely used type today. In addition to their more attractive design, aluminum rims are also corrosion-free and much lighter than steel rims, making it easier to achieve acceleration and top speed. Larger rims allow for wider tires. This can improve vehicle traction and stability, especially when driving at high speeds or on uneven roads. Wheel traction is one of the vehicle's capabilities to push a load. Traction is a large force that determines the power of the engine, wheels, and wheel load to turn on between the wheels and the road. Traction force analysis needs to be done to get an efficient traction force. This study uses an experimental method with a motorcycle that turns on so that the rear wheel rotates and a traction force occurs between the tire surface and the road surface. This study uses rim sizes of 17x1.60, 17x1.85 and 17x2.15. The results of the study show that differences in rim sizes affect the traction force on the rear wheels, where the highest traction force occurs on the rim size of 17 x 2.15 inches of 2399 Newtons and the lowest traction force occurs on the rim ring of 17 x 1.60 inches of 1438.7 Newtons.